GAMBARAN TINGKAT DEPRESI MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH ANGKATAN 2017 - Anissa, Mutiara; Akbar, Resti Rahmadika (E-Jurnal Medika Udayana; Vol 11 No 8 (2022): E-Jurnal Medika Udayana, 2022)
Depression is a mental disorder that is mostly found in the general population. Medical education in Indonesia aims to produce doctors based on the needs of public health services. This process causes medical students to face various kinds of stressors, such as a large academic load, time pressure, adjustment to the campus environment, and relationships with peers. If exposure to stress continues for a long period, this condition can lead to depression. If medical students experience depression, this condition can certainly affect their academic performance and their ability to become prospective general practitioners. Methods: This research is a descriptive study with consecutive sampling. The research respondents were 83 students of the Faculty of Medicine at Baiturrahmah University Class of 2017. Respondents will fill out the Depression, Anxiety, and Stress Scale (DASS) 21 questionnaire to measure depression symptoms. Results: In the study, it was found that 75.9% of respondents were women, most of the respondents (80.7%) entered the medical faculty at their own will and during the education period, 90.4% of respondents lived alone either in boarding houses or rented houses.   Conclusions: This questionnaire has been validated in Indonesian. Respondents experienced the most depressive symptoms and were at the level of mild depression. Based on the above results, a better educational atmosphere that supports the educational process is very important to prevent depression in students.